Simultaneous 68Ga DOTATATE Positron Emission Tomography/Magnetic Resonance Imaging in Meningioma Target Contouring: Feasibility and Impact Upon Interobserver Variability Versus Positron Emission Tomography/Computed Tomography and Computed Tomography/Magnetic Resonance Imaging. Issue 7 (July 2017) - Maclean, J.; Fersht, N.; Sullivan, K.; Kayani, I.; Bomanji, J.; Dickson, J.; O'Meara, C.; Short, S.
Abstract: Aims: The increasing use of highly conformal radiation techniques to treat meningioma confers a greater need for accurate targeting. Several groups have shown that positron emission tomography/computed tomography (PET/CT) information alters meningioma targets contoured by single observers, but whether this translates into improved accuracy has not been defined. As magnetic resonance imaging (MRI) is the cornerstone of meningioma target contouring, simultaneous PET/MRI may be superior to PET/CT. We assessed whether 68 Ga DOTATATE PET imaging (from PET/CT and PET/MRI) reduced interobserver variability (IOV) in meningioma target volume contouring. Materials and methods: Ten patients with meningioma underwent simultaneous 68 Ga DOTATATE PET/MRI followed by PET/CT. They were selected as it was anticipated that target volume definition in their cases would be particularly challenging. Three radiation oncologists contoured target volumes according to an agreed protocol: gross tumour volume (GTV) and clinical target volume (CTV) on CT/MRI alone, CT/MRI+PET(CT) and CT/MRI+PET(MRI). GTV/CTV Kouwenhoven conformity levels (KCL), regions of contour variation and qualitative differences between PET(CT) and PET(MRI) were evaluated. Results: There was substantial IOV in contouring. GTV mean KCL: CT/MRI 0.34, CT/MRI+PET(CT) 0.38, CT/MRI+PET(MRI) 0.39 ( P  = 0.06). CTV mean KCL: CT/MRI 0.31, CT/MRI+PET(CT) 0.35, CT/MRI+PET(MRI) 0.35 ( P  = 0.04 for all groups; P  > 0.05 for individual pairs). One observer consistently contoured largest and one smallest. Observers rarely decreased volumes in relation to PET. Most IOV occurred in bone followed by dural tail, postoperative bed and venous sinuses. Tumour edges were qualitatively clearer on PET(MRI) versus PET(CT), but this did not affect contouring. Conclusion: IOV in contouring challenging meningioma cases was large and only slightly improved with the addition of 68 Ga DOTATATE PET. Simultaneous PET/MRI for meningioma contouring is feasible, but did not improve IOV versus PET/CT. Whether volumes can be safely reduced according to PET requires evaluation. Highlights: Baseline levels of interobserver variability in meningioma target volume definition using CT/MRI were high. Simultaneous 68 Ga DOTATATE PET/ MRI co-registered to CT/MRI was feasible but only slightly improved contouring consistency. Meningioma borders were slightly clearer on PET from simultaneous PET/MRI than sequential PET/CT, but this did not affect contouring. 68 Ga DOTATATE PET use in target volume definition for meningiomas may have a role in select cases. Future studies to clarify the sensitivity of PET in meningiomas are required.